Analysis of metal pollution index in waters in the central Java area, Indonesia - Sapta Suhardono; Iva Yenis Septiariva; Mega Mutiara Sari; I Wayan Koko Suryawan (., 2022)
Central Java is one of the regions in Indonesia with a lot of water resources that must be appropriately managed. In addition, metal content in water bodies in Central Java must now be assessed to prevent health impacts that may be measurable. One of the methods to analyze the management of water bodies is the water quality index method. This study aimed to examine the water quality index due to metal contamination in water bodies in Central Java. Metal measurements were carried out using the AAS (Atomic Absorption Spectrophotometry) method. The value of the water quality index using the water quality index method for waters in Central Java in 2015-2018 was categorized to mild to moderately polluted, and only 2 locations were measured as heavily polluted. Two areas that are included in the heavily polluted category were the waters of Bulakan and Bojonegoro in 2016. To determine the cause of why the water quality index value being classified as moderately polluted and lightly polluted, we must look at the metal parameters that contribute the most to the index value. These parameters can be initial information on the pollutant source that causes pollution.